UNDOING STEREOTYPES: COUNTER-STEREOTYPING STRATEGY BASED ON THE MADURESE CULTURAL IDENTITIES - Medhy Aginta Hidayat; Nikmah Suryandari (Alfuad: Jurnal Sosial Keagamaan, 2022)
This study examines the construction of negative stereotypes and the efforts to build counter-stereotypes for the Madurese by utilizing their cultural identities. The Madurese are known as one of the ethnic groups in Indonesia who often become the object of negative stereotypes. A number of negative stereotypes of the Madurese include stubbornness, stiffness, temperamental, vengefulness, unruly, lack of respect for others, irritability, loud voices, lack of courtesy, lack of education, and easily commit acts of violence. Through the strategy of counter-stereotypes, it is hoped that the negative stereotypes attached to Madurese individuals will gradually diminish. This study uses a qualitative approach that focuses on the views and experiences of Madurese high school students in Madura. The data were obtained through field observations and in-depth interviews. This study found that negative stereotypes of Madurese are formed by the internal factors (from within individuals of the Madurese) and external factors (from the outside view of other ethnicities). The efforts to build positive stereotypes of Madurese can be carried out more effectively through the intervention of education at schools. The results of this study are expected to become a model to change negative stereotypes and build positive perceptions of certain ethnic groups.